Efficacy and Safety of Monoclonal Antibody Against Calcitonin Gene-Related Peptide or Its Receptor for Migraine: A Systematic Review and Network Meta-analysis - Wang, Xing; Chen, Yuqi; Song, Jinlei; You, Chao (Frontiers in Pharmacology, 2021)
Background The optimal monoclonal antibody against calcitonin gene-related peptide (CGRP) for adult patients with migraine has yet to be determined. Therefore, we aimed to compare the effectiveness of different monoclonal antibodies against CGRP or its receptor for adult patients with migraine through a network meta-analysis of randomized controlled trials. Methods We systematically searched the MEDILNE, Embase, ClinicalTrials.gov and Cochrane Library databases for relevant publications from inception until October 30, 2020. Only randomized clinical trials of adults with migraine that assessed any CGRP monoclonal antibody and reported clinical outcomes were included. The primary outcomes were changes in monthly migraine days (MMDs) and treatment-emergent adverse events (TEAEs). Results We initially retrieved 2,070 publications, and ultimately, 18 randomized clinical trials totaling 8,926 patients were included. In terms of efficacy, eptinezumab (MD -1.43, 95% CrI -2.59 to -0.36), erenumab (MD -1.61, 95% CrI -2.40 to -0.84), fremanezumab (MD -2.19, 95% CrI -3.15 to -1.25), and galcanezumab (MD -2.10, 95% CrI -2.76 to -1.45) significantly reduced MMDs compared with placebo. In terms of safety, only galcanezumab increased the incidences of TEAEs (RR 1.11, 95% CrI 1.01 to 1.22) and serious adverse events (RR 2.95, 95% CrI 1.41 to 6.87) compared with placebo. Conclusions Most drugs performed similarly and were superior to placebo in most of our analyses. Further head-to-head research on different types of CGRP monoclonal antibodies is necessary to validate the present findings.